Validation Checklist for Massive Vaccination Centers - Capolongo, S.; Brambilla, A.; Girardi, A.; Signorelli, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Starting from the minimum requirements indicated by Lombardy Region, a validation checklist has been developed by experts in design, healthcare layout planning, hygiene and public health, planning and compliance, in order to provide managers of COVID-19 massive vaccination centers with a useful and easy-to-use tool to ensure quality, safety and efficiency of the different activities performed.